Manajemen Anastesi pada Laminektomi pada Cedera Vertebra Servikal V-VI di RSUD Dr. H. Abdul Moeloek, Bandar Lampung - Fairuz Nabila Afia; Bambang Eko Subekti (Medula, 2020)
Cervical spinal cord injuries can occur directly or inderectly that can cause neurological disorder or death. Cervical injuries occur 2-3% of all cedera events and 8,2% of all cederas that cause of death. Symptoms of cervikal cedera can be partial or loss of limb movements and / or sensation that can be in calssified as complete or incomplete. A 40 year-old man with complaints of weakness and tingling in all four limbs since 3 days before entering the hospital, patient had history of motorcycle accidents. Resuscitation and protection of cervical vertebrae have been carried out, which aim to preventing or minimize other damage to the nervous system after servikal injury , increase the patient's recovery and planning specifically during perioperative, including airway management, induction, general anesthesia, and recovery phase. The purpose of this case report is to find out the anesthetic management in the form of planning, description of clinical problems, identifying the risk factors that cause and providing the best management for patients.